A Guide to PIN1 Function and Mutations Across Cancers - El Boustani, Maguie; De Stefano, Lucia; Caligiuri, Isabella; Mouawad, Nayla; Granchi, Carlotta; Canzonieri, Vincenzo; Tuccinardi, Tiziano; Giordano, Antonio; Rizzolio, Flavio (Frontiers in Pharmacology, 2019)
PIN1 is a member of a family of peptidylprolyl isomerases that bind phosphoproteins and catalyze the rapid cis-trans isomerization of proline peptidyl bonds, resulting in an alteration of protein structure, function and stability. PIN1 is overexpressed in human cancers, suggesting it promotes tumorigenesis, but depending on the cellular context, it also acts as a tumor suppressor. Here, we review the role of PIN1 in cancer and the regulation of PIN1 expression, and catalog the single nucleotide polymorphisms and mutations in PIN1 gene associated with cancer. In addition, we provide a 3D model of the protein to localize the mutated residues.